Common arterial trunk: pathomorphological changes of unoperated cardiac defect in adulthood - V. I. Hryhoriichuk; Yu. I. Kuzyk; O. I. Boiko (Zaporozhye State Medical University, 2018)
Congenital heart defects in adulthood constitute the sufficient proportion of cardiac pathology. The common arterial trunk (CAT) is one of the сongenital cardiac defects that is described in the adult population. Without surgical intervention, patients who survived become inoperable quickly due to the development of early congestive heart insufficiency and pulmonary hypertension. The purpose of the research is to analyze the autopsy case of unoperated congenital cardiac defects in adulthood. Materials and methods. The pathomorphological analysis of the case of death of a 33-year-old male with untreated complex congenital heart defect - CAT, ventricular septal defect, Eisenmenger's syndrome was made using standard and elective histological techniques. Results. In the forensic examination of the body of the deceased 33-year-old male, congenital heart defect was diagnosed as CAT and ventricular septal defect. Coronary, pulmonary and major arteries of a large circle of blood circulate from the CAT. Congenital heart defect has been complicated by the development of cardiomegaly (heart weight 1500 g) with myocardial hypertrophy of both ventricles and led to decompensation of cardiac activity. During the pathohistological examination of the valve of the CAT we determined the foci of fibrinoid necrosis, myxomatosis, single accumulation of lymphocytes, focal fibrosis. In the myocardium of the right and left ventricles we observed hypertrophy, focal contraction and fragmentation of cardiomyocytes, expressed intramuscular edema, sclerosis of the walls of the small intramural arteries with perifocal areas of vacuolar degeneration of cardiomyocytes, stromal cardiosclerosis, isolated interstitial infiltration of lymphocytes, dilatation of lymphatic vessels. In the pulmonary tissue diffuse hemosiderosis, multiple intravalveolar hemorrhages, sclerosis of the small pulmonary arteries with the formation of two- and three-sided lumen, sclerosis of interalveolar membranes were detected. Morphological changes in the myocardium and lungs confirm prolonged congestive heart failure and pulmonary hypertension. Conclusions. We describe a unique case of long-term survival of a patient with CAT without surgical intervention. The complex of pathomorphological changes of the described case testifies to cardiovascular remodeling, which is the base of hemodynamic evolution of complex congenital heart disease and allowed the man to live up to 33 years without surgical intervention.